Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery

By doping lithium-containing and sulfur-containing compounds into the carbon coating of lithium-ferrous manganese phosphate positive electrode material and doping chromium ions in the core, the low conductivity and manganese dissolution problems of lithium-ferrous manganese phosphate positive electrode material are solved, significantly improving the battery's performance and cycle life.

CN119627074APending Publication Date: 2025-03-14福建龙净储能电池有限公司

Patent Information

Application Number
CN202411789271.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have low ion conductivity, poor charging and discharging performance, and manganese elements dissolve at high temperatures, resulting in a short cycle life.

Method used

The lithium manganese iron phosphate positive electrode material doped in the carbon coating layer is used to increase the electron conductivity and lithium ion diffusion rate through doping of the carbon coating layer, and reduce the dissolution of manganese through chromium ion doping.

Benefits of technology

It improves the capacity, circulation and rate performance of the battery, extends the high-temperature cycle life, and improves the structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery. The lithium manganese iron phosphate positive electrode material comprises a lithium manganese iron phosphate inner core and a carbon coating layer coating the surface of the lithium manganese iron phosphate inner core; and a lithium-containing compound and a sulfur-containing compound are doped in the carbon coating layer. The lithium manganese iron phosphate positive electrode material provided by the invention is high in electronic conductivity and higher in lithium ion diffusion rate, and moreover, the dissolution of manganous ions is reduced, and the structural stability is maintained, so that the capacity, the cycle performance and the rate performance of a battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] With the application of lithium-ion batteries, commercial products have higher and higher requirements for the cost performance of lithium-ion batteries, which is mainly reflected in the increasingly fierce competition among battery manufacturers for the cost per watt-hour of batteries. In recent years, the market share of lithium iron phosphate has surpassed that of ternary batteries. On the one hand, it is because lithium iron phosphate is safer, and on the other hand, it is because the price of lithium iron phosphate is lower. With the development of material technology, lithium iron manganese phosphate has received more and more attention from the industry.

[0003] Lithium iron manganese phosphate is a product of lithium iron phosphate and lithium manganese phosphate. It is the same as lithium iron phosphate in structure, and its crystal form is an orderly olivine structure. Therefore, it has the same high structural stability as lithium iron phosphate. Manganese is cheaper than precious metals cobalt and nickel, and the cost of raw material preparation is low. Coupled with the high safety performance and high thermal stability similar to lithium iron, it can be said that it has the advantages of both lithium iron phosphate and lithium manganese phosphate, and can also make up for the shortcoming of low energy density of lithium iron phosphate. Therefore, it is also known as the "upgraded version of lithium iron phosphate". The theoretical capacity of lithium iron manganese phosphate is the same as that of lithium iron phosphate, which is 170mAh / g; but the voltage platform of lithium iron manganese phosphate material is 4.1V, which is much higher than the 3.4V of lithium iron phosphate. The platform voltage has increased by 20%, which has led to a 20% increase in the density of the same battery capacity compared to lithium iron phosphate material.

[0004] However, the conductivity of lithium manganese iron phosphate is lower than that of lithium iron phosphate, and its charge and discharge rate performance is also worse. In addition, the manganese content in lithium manganese iron phosphate is relatively high, which will cause a large amount of manganese to dissolve during high temperature, thereby shortening the high temperature cycle life. At present, the conventional operation is to improve the conductivity and cycle problems of materials through doping, carbon coating, and nano-processing similar to lithium iron. However, general modification methods such as doping and nano-processing are difficult to significantly improve such problems.

[0005] CN115911365A provides a carbon-coated lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery, which relates to the technical field of battery materials. The preparation method of the carbon-coated lithium iron manganese phosphate positive electrode material comprises first mechanically mixing an organic carbon source and a precursor uniformly, then sintering under suitable sintering conditions, and then subjecting the obtained coating to at least one carbon coating to finally obtain a carbon-coated lithium iron manganese phosphate positive electrode material. However, the pure carbon coating layer is not conducive to the passage of ions and cannot improve the ionic conductivity of the material.

[0006] CN107046128A discloses a method for preparing a lithium iron manganese phosphate composite material, wherein the lithium iron manganese phosphate composite material comprises lithium iron manganese phosphate and a hydrophobic material coated on the surface of the lithium iron manganese phosphate. Since the hydrophobic material is coated on the surface of the lithium iron manganese phosphate, the coating material is insoluble in water and resistant to electrolyte; therefore, compared with the traditional lithium iron manganese phosphate material, the lithium iron manganese phosphate composite material can improve the problem of the lithium iron manganese phosphate battery absorbing water easily, but the conductivity of the lithium iron manganese phosphate composite material is not significantly improved.

[0007] CN111710846A discloses an anion-doped lithium manganese iron phosphate material, which obtains a silicon-containing lithium manganese iron phosphate precursor by a one-step method and then sintered to obtain a high-density product. Due to the presence of silicon, the ionic conductivity of the lithium manganese iron phosphate material is poor.

[0008] Therefore, how to improve the ion diffusion rate of lithium manganese iron phosphate and effectively inhibit the dissolution of manganese is an urgent research goal. Summary of the invention

[0009] In view of the shortcomings of the prior art, the object of the present invention is to provide a lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery. The lithium iron manganese phosphate positive electrode material provided by the present invention has high electronic conductivity, faster ion lithium ion diffusion rate, reduced dissolution of manganese ions, maintained structural stability, thereby improving the capacity, cycle and rate performance of the battery.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a lithium iron manganese phosphate positive electrode material, which includes a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core; the carbon coating layer is doped with a lithium-containing compound and a sulfur-containing compound.

[0012] The lithium iron manganese phosphate positive electrode material provided by the present invention has a small particle size, high purity, and a large specific surface area. The carbon coating layer and the lithium-containing compound and the sulfur-containing compound in the carbon coating layer are co-doped for synergistic coordination, wherein the lithium-containing compound can supplement lithium at the local lithium-deficient part of the material and improve the crystallinity of the material, while the sulfur-containing compound further improves the electronic conductivity of the carbon coating layer, reduces the diffusion barrier of the lithium ion surface, increases the lithium ion diffusion rate, and alleviates the manganese dissolution phenomenon of the lithium iron manganese phosphate core to a certain extent; thereby improving the capacity, cycle and rate performance of the battery.

[0013] In the present invention, the specific types of lithium-containing compounds and sulfur-containing compounds are closely related to the raw materials added thereto, so no special limitation is imposed on the specific types of the compounds.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the lithium manganese iron phosphate core is also doped with chromium ions.

[0016] In the present invention, by doping chromium ions in the lithium iron manganese phosphate core, and the chromium element exists in the core in the form of ions rather than compounds, the dissolution of manganese ions can be reduced at high temperatures, the Jan-Taylor effect of the lithium iron manganese phosphate positive electrode material in the cycle process can be suppressed, the structural stability of the positive electrode material can be maintained, and the cycle performance and rate performance of the battery can be further improved; and the chromium ion doping and the structure in the carbon coating layer also play a synergistic role, which better improves the capacity, cycle and rate performance of the battery.

[0017] Preferably, the median particle size D50 of the lithium manganese iron phosphate core is 450nm~800nm450nm~800nm, for example, 450nm, 475nm, 500nm, 525nm, 550nm, 575nm, 600nm, 625nm, 675nm, 700nm, 725nm, 750nm, 775nm or 800nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the lithium-containing compound comprises an organic lithium compound.

[0019] In the present invention, the carbon coating layer is doped with an organic lithium compound, which is more conducive to replenishing lithium in the local lithium-deficient parts of the lithium iron manganese phosphate material and improving the crystallinity of the material.

[0020] In a second aspect, the present invention provides a method for preparing the lithium manganese iron phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0021] A carbon source, a lithium source and a sulfur source are mixed at one time to obtain a doped carbon source;

[0022] Then, the carbon source, the first lithium source, the phosphorus source, the manganese source and the iron source are mixed and doped for a second time, and reacted to obtain the lithium manganese iron phosphate positive electrode material.

[0023] The preparation method provided by the present invention first mixes the carbon source with the doped lithium and sulfur source, and then mixes the raw materials in the lithium iron manganese phosphate core, which can better achieve uniform coating of the carbon coating layer and uniform doping and coating of the lithium-containing compound and the sulfur-containing compound. Through a simple processing process, a lithium iron manganese phosphate positive electrode material in which the lithium-containing compound and the sulfur element are simultaneously doped in the carbon coating layer can be obtained.

[0024] It should be noted that the ratio of the addition amount of the first lithium source, phosphorus source, manganese source and iron source in the present invention can be adaptively adjusted according to the ratio of lithium, manganese, phosphorus and iron in the target core; the chemical formula of the lithium manganese iron phosphate core without any doping treatment is LiMn x Fe 1-x PO4, 0<x<1, for example 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the molar ratio of the carbon source to the sulfur source is 50:(0.5-2), for example 50:0.5, 50:0.6, 50:0.7, 50:0.8, 50:0.9, 50:1, 50:1.1, 50:1.2, 50:1.3, 50:1.4, 50:1.5, 50:1.6, 50:1.7, 50:1.8, 50:1.9 or 50:2, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In the present invention, by adjusting the molar ratio of the carbon source to the sulfur source to 50:(0.5-2), the doping amount of sulfur in the carbon coating layer is adjusted, thereby having a better ion diffusion rate; this not only ensures that the structural stability of the material is better, but also obtains a more excellent electrical conductivity.

[0027] Preferably, the molar ratio of the carbon source to the doped lithium source is 50:(0.5-2), for example 50:0.5, 50:0.6, 50:0.7, 50:0.8, 50:0.9, 50:1, 50:1.1, 50:1.2, 50:1.3, 50:1.4, 50:1.5, 50:1.6, 50:1.7, 50:1.8, 50:1.9 or 50:2, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In the present invention, by adjusting the molar ratio of the carbon source to the doped lithium source to 50:(0.5-2), the optimal ratio for increasing the capacity of the battery is explored to prevent the risk of thermal runaway of the battery due to excessive lithium.

[0029] Preferably, the doping lithium source includes any one of lithium tert-amyl alcoholate, lithium cyclopentadienyl, lithium tetramethylcyclopentadienyl, lithium dimethylamide, lithium phenoxide, dilithium phthalocyanine, lithium dicyclohexylamide or lithium 2,2,6,6-tetramethylpiperidinate, or a combination of at least two thereof.

[0030] Preferably, the sulfur source includes but is not limited to dibenzyl disulfide and / or thiourea.

[0031] Preferably, the carbon source includes, but is not limited to, one or more of citric acid, ascorbic acid, starch, potato starch, sucrose or glucose.

[0032] Preferably, the primary mixing includes liquid phase mixing, and the liquid phase mixing includes: primary mixing of a carbon source, a doped lithium source, a sulfur source and a solvent to obtain a doped carbon source.

[0033] The present invention does not limit the type of solvent, and is applicable to any type of the above-mentioned raw material mixture. For example, the solvent includes water and / or ethanol.

[0034] Preferably, when the raw materials mixed once further include a solvent, the obtained secondary mixture is a gel-state substance.

[0035] The present invention adds a solvent during the mixing process to obtain a gel-state substance, that is, the lithium manganese iron phosphate positive electrode material is prepared by a sol-gel method, so that the prepared material has higher purity, smaller particle size and larger specific surface area.

[0036] It should also be noted that the preparation process of the gel-state substance by the sol-gel method in the present invention is a conventional technical scheme, that is, the mixed solution is heated and stirred at 50 to 80°C (for example, 50°C, 60°C, 70°C or 80°C, etc.) to obtain a gel, and then the gel is dried and ground to obtain the gel-state substance to be reacted.

[0037] Preferably, the reaction comprises heat treating the secondarily mixed material.

[0038] Preferably, the heat treatment comprises sequentially performing a first heat treatment and a second heat treatment;

[0039] Preferably, the temperature of the first heat treatment is 250-400°C, such as 250°C, 300°C, 350°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the time of the first heat treatment is 1 to 10 hours, for example 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the temperature of the second heat treatment is 600-900°C, for example 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the time of the second heat treatment is 5 to 24 h, for example 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the product obtained after the reaction is subjected to ion implantation of chromium ions.

[0044] In the present invention, the product after the reaction includes a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core, and the core is doped with chromium ions by ion implantation, so that precise doping of various parts of the material can be achieved without affecting the olive-shaped structure of the lithium iron manganese phosphate, reducing the dissolution of manganese ions, and inhibiting the Jan-Taylor effect of the lithium iron manganese phosphate during the cycle, which can better maintain the structural stability of the lithium iron manganese phosphate.

[0045] Preferably, the product after the reaction is firstly ground and then the chromium ions are implanted.

[0046] Preferably, during the ion implantation process, the ion voltage is 90-120 keV, for example 90 keV, 95 keV, 100 keV, 105 keV, 110 keV, 115 keV or 120 keV, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0047] Preferably, during the ion implantation process, the amount of chromium ions implanted is 5×10 10 ions / cm 2 ~9×10 11 ions / cm 2 , for example 6×10 10 ions / cm 2 ,7×10 10 ions / cm 2 , 8×10 10 ions / cm 2 ,9×10 10 ions / cm 2 , 1×10 11 ions / cm 2 , 2×10 11 ions / cm 2 , 3×10 11 ions / cm 2 , 4×10 11 ions / cm 2 , 5×1011 ions / cm 2 , 6×10 11 ions / cm 2 ,7×10 11 ions / cm 2 , 8×10 11 ions / cm 2 or 9×10 11 ions / cm 2 The above range is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0048] In the present invention, during the ion implantation process, the amount of chromium ions implanted is regulated within a range of 5×10 10 ions / cm 2 ~9×10 11 ions / cm 2 When the temperature of the lithium manganese iron phosphate cathode material is increased, the effect is more obvious and the effect is more excellent. It will not hinder the effective performance of the material itself and the carbon coating layer.

[0049] Preferably, during the ion implantation process, the vacuum degree is less than 1×10 -5 Pa.

[0050] As a preferred technical solution, the preparation method comprises the following steps:

[0051] Mixing a carbon source, a lithium source, a sulfur source and a solvent at one time, wherein the molar ratio of the carbon source to the sulfur source is 50:(0.5-2), and the molar ratio of the carbon source to the doped lithium source is 50:(0.5-2), to obtain a doped carbon source;

[0052] secondary mixing and doping the carbon source, the first lithium source, the phosphorus source, the manganese source and the iron source to obtain a gel-state substance;

[0053] The gel-state substance is subjected to a first heat treatment at 250 to 400° C. for 1 to 10 hours, and then the temperature is raised to 600 to 900° C. for a second heat treatment for 5 to 24 hours to obtain a reaction product;

[0054] The reaction product is ground to a vacuum degree of less than 1×10 -5 Pa, the ion implantation voltage was 90-120 keV, and the ion implantation volume was 5×10 10 ions / cm 2 ~9×10 11 ions / cm 2 , obtaining the lithium manganese iron phosphate positive electrode material.

[0055] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material as described in the first aspect or the lithium iron manganese phosphate positive electrode material prepared by the preparation method as described in the second aspect.

[0056] It should also be noted that the specific material types of the first lithium source, phosphorus source, manganese source and iron source in the present invention are all selected according to conventional technical solutions, and the present invention is applicable to all types of raw materials that can be used for the preparation of lithium manganese iron phosphate.

[0057] Specifically, the lithium source may be one or more of lithium nitrate, lithium acetate, lithium formate, lithium hydroxide, lithium carbonate, lithium chloride or lithium fluoride.

[0058] The phosphorus source may be one or more of ferric phosphate, ammonium dihydrogen phosphate, dihydrogen phosphate or phosphoric acid.

[0059] The manganese source may be one or more of manganous acetate, manganese carbonate, acid manganese phosphate, manganese phosphate or manganese oxalate.

[0060] The iron source may be one or more of ferric nitrate, ferrous oxalate or ferrous chloride.

[0061] In addition, the reaction process of lithium manganese iron phosphate provided by the present invention is carried out under a protective atmosphere (nitrogen atmosphere or inert gas atmosphere) to prevent manganese and iron from being oxidized.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The lithium iron manganese phosphate positive electrode material provided by the present invention has a small particle size, high purity, and a large specific surface area. The carbon coating layer and the lithium-containing compound and the sulfur-containing compound in the carbon coating layer are co-doped for synergistic coordination, wherein the lithium-containing compound can supplement lithium at the local lithium-deficient part of the material and improve the crystallinity of the material, while the sulfur-containing compound further improves the electronic conductivity of the carbon coating layer, reduces the diffusion barrier of the lithium ion surface, increases the lithium ion diffusion rate, and alleviates the manganese dissolution phenomenon of the lithium iron manganese phosphate core to a certain extent; thereby improving the capacity, cycle and rate performance of the battery. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0066] In the description of the embodiments of the present application, the technical terms "first", "second", "first", "secondary", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0067] Example 1

[0068] The present embodiment provides a lithium iron manganese phosphate positive electrode material, which includes a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core; the carbon coating layer is doped with cyclopentadienyl lithium and sulfur element, and the core is doped with chromium ions.

[0069] The preparation method of the lithium manganese iron phosphate positive electrode material is as follows:

[0070] S1: At room temperature, glucose, dibenzyl disulfide and cyclopentadienyl lithium were weighed in a molar ratio of 50:1:1, and the above substances were dissolved in 2000 mL of a mixed solvent, wherein the mixed solvent includes deionized water and ethanol in a volume ratio of 1:1, and the mixture was continuously stirred at 25° C. for 2 h to obtain a first mixed solution;

[0071] S2: lithium hydroxide as a lithium source, phosphoric acid as a phosphorus source, manganese acetate as a manganese source and ferrous chloride as an iron source are weighed according to a molar ratio of Li:P:Mn:Fe of 1:1:0.6:0.4, and then added to the first mixed solution of S1, and dissolved by stirring at 70°C at a speed of 2000 rpm / min to obtain a light yellow gel solution, and the light yellow gel solution is further stirred for 1 hour, and then the gel is transferred to an oven and dried at 90°C overnight to obtain a dry gel body, and then the dry gel body is ground to obtain a uniform powder, and then first heat-treated at 350°C for 5 hours in a nitrogen environment, and then second heat-treated at 650°C for 10 hours to obtain a double-modified lithium manganese iron phosphate (the product after the reaction includes an undoped lithium manganese iron phosphate core and a carbon coating layer coated on the surface of the lithium manganese iron phosphate core, and the carbon coating layer is doped with cyclopentadiene lithium and sulfur);

[0072] S3: Grind the double-modified lithium manganese iron phosphate obtained in S2 to obtain uniform powder. -5 Pa, chromium ions were injected (injection parameters: ion voltage 110 KeV, ion injection volume 6×10 10 ions / cm 2 ), to obtain the lithium manganese iron phosphate positive electrode material.

[0073] Example 2

[0074] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:0.5:1.

[0075] The rest of the preparation methods and parameters were the same as those in Example 1.

[0076] Example 3

[0077] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:1.5:1.

[0078] The rest of the preparation methods and parameters were the same as those in Example 1.

[0079] Example 4

[0080] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:2:1.

[0081] The rest of the preparation methods and parameters were the same as those in Example 1.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:1:0.5.

[0084] The rest of the preparation methods and parameters were the same as those in Example 1.

[0085] Example 6

[0086] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:1:1.5.

[0087] The rest of the preparation methods and parameters were the same as those in Example 1.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, glucose, dibenzyl disulfide and cyclopentadienyl lithium are weighed according to a molar ratio of 50:1:2.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Example 8

[0092] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the implantation parameters are: ion voltage 110 KeV, ion implantation volume 6×10 9 ions / cm 2 .

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Example 9

[0095] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the implantation parameters are: ion voltage 110 KeV, ion implantation volume 3×10 10 ions / cm 2 .

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Example 10

[0098] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the implantation parameters are: ion voltage 110 KeV, ion implantation volume 8×10 10 ions / cm 2 .

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Embodiment 11

[0101] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the implantation parameters are: ion voltage 110 KeV, ion implantation volume 1×10 11 ions / cm 2 .

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Example 12

[0104] The difference between this embodiment and embodiment 1 is that the lithium manganese iron phosphate positive electrode material provided in this embodiment is not doped with chromium ions.

[0105] In the preparation method, step S3 is not performed.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] Comparative Example 1

[0108] The difference between this comparative example and Example 1 is that in the lithium manganese iron phosphate positive electrode material provided in this comparative example, sulfur is not doped in the carbon coating layer.

[0109] In step S1 of the preparation method, dibenzyl disulfide is not added.

[0110] The rest of the preparation methods and parameters were the same as those in Example 1.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 1 is that in the lithium manganese iron phosphate positive electrode material provided in this comparative example, organic lithium doping is not performed in the carbon coating layer.

[0113] In step S1 of the preparation method, cyclopentadienyllithium is not added.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Comparative Example 3

[0116] The difference between this comparative example and Example 1 is that in the lithium manganese iron phosphate positive electrode material provided in this comparative example, chromium ions in the core are not doped, and organic lithium and sulfur elements in the carbon coating layer are not doped.

[0117] In step S1 of the preparation method, dibenzyl disulfide and cyclopentadienyl lithium are not added; meanwhile, the preparation process of step S3 is not performed.

[0118] The rest of the preparation methods and parameters were the same as those in Example 1.

[0119] The powder resistivity of the lithium iron manganese phosphate positive electrode materials provided in Examples 1-12 and Comparative Examples 1-3 was tested: At 25°C, the lithium iron manganese phosphate prepared in the Examples and Comparative Examples was tested using a four-probe powder resistivity meter, and the resistivity value was recorded when the pressure reached 20 MPa. The test results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] Battery preparation:

[0124] The lithium manganese iron phosphate positive electrode material, PVDF glue, carbon black (SP) and CNT provided in Examples 1-12 and Comparative Examples 1-3 were respectively weighed at a mass ratio of 95:2:0.8:0.6, with a total weight of 10 g. The weighed materials were poured into a ball mill, N-methylpyrrolidone was added, and the mixture was stirred for 10 min using a high-speed swing ball mill to obtain a uniformly stirred slurry, which was then evenly coated on the current collector aluminum foil, dried in a vacuum drying oven at 105 ° C for 4 h, and rolled to 2.35 mg / cm 3 After reaching the compaction density, die-cutting and weighing are carried out, and the cells are dried in a vacuum oven at 105°C for 2 hours and then put into a glove box for assembly into half-cells.

[0125] Using metallic lithium as the negative electrode, the button cell was assembled in an argon-filled glove box according to the order of placing the negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm (Celgard2400 purchased from Celgard), electrolyte (1 mol / L LiPF6 electrolyte (the volume ratio of ethylene carbonate and diethyl carbonate in the solvent = 1:1)), positive electrode (electrode sheet) and positive electrode shell. Finally, the battery was packaged with a battery sealing machine.

[0126] The battery prepared above was subjected to performance testing.

[0127] (I) Charge and discharge capacity: At 25°C, the lithium-ion battery was left to stand for 12 h, then charged at a constant current rate of 0.1C to a voltage of 4.2 V, left to stand for 5 minutes, and then discharged at a constant current rate of 0.1C to 2.5 V, left to stand for 5 minutes, and the first cycle discharge specific capacity was recorded. The test results are shown in Table 2.

[0128] Table 2

[0129]

[0130]

[0131] (II) Cycle performance test: At 25°C, the lithium-ion battery was charged at a constant current rate of 1C to a voltage of 4.2V, left to stand for 5 minutes, and then discharged at a rate of 1C to 2.5V, left to stand for 5 minutes. The above is one charge and discharge cycle. The lithium-ion battery was charged and discharged 100 times at 25°C and 45°C under the above conditions and the discharge specific capacity and capacity retention rate were recorded. The test results are shown in Table 3.

[0132] Table 3

[0133]

[0134]

[0135] (III) Rate performance: Charge and discharge were performed at current rates of 0.1C, 0.33C, 0.5C, and 1C at 25°C, and the discharge specific capacity at each rate was recorded; the test results of the above tests are shown in Table 4.

[0136] Table 4

[0137]

[0138]

[0139] In summary, the lithium iron manganese phosphate positive electrode material provided by the present invention has a small particle size, high purity, and a large specific surface area. The carbon coating layer and the lithium-containing compound and the sulfur-containing compound in the carbon coating layer are co-doped for synergistic cooperation, wherein the lithium-containing compound can supplement lithium at the local lithium-deficient parts of the material and improve the degree of crystallization of the material, while the sulfur-containing compound further improves the electronic conductivity of the carbon coating layer, reduces the diffusion barrier on the surface of lithium ions, increases the diffusion rate of lithium ions, and alleviates the manganese dissolution phenomenon in the core of the lithium iron manganese phosphate to a certain extent; the capacity, cycle and rate performance of the battery are improved.

[0140] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium iron manganese phosphate positive electrode material comprises a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core; the carbon coating layer is doped with a lithium-containing compound and a sulfur-containing compound.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The lithium manganese iron phosphate core is also doped with chromium ions; Preferably, the median particle size D50 of the lithium manganese iron phosphate core is 450nm to 800nm.

3. The lithium iron manganese phosphate positive electrode material according to claim 1 or 2, characterized in that: The lithium-containing compound includes an organic lithium compound.

4. A method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: A carbon source, a lithium source and a sulfur source are mixed at one time to obtain a doped carbon source; Then, the carbon source, the first lithium source, the phosphorus source, the manganese source and the iron source are mixed and doped for a second time, and reacted to obtain the lithium manganese iron phosphate positive electrode material.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the carbon source to the sulfur source is 50:(0.5-2); Preferably, the molar ratio of the carbon source to the doped lithium source is 50:(0.5-2); Preferably, the doping lithium source includes any one of lithium tert-amyl alcoholate, lithium cyclopentadienyl, lithium tetramethylcyclopentadienyl, lithium dimethylamide, lithium phenoxide, dilithium phthalocyanine, lithium dicyclohexylamide or lithium 2,2,6,6-tetramethylpiperidinate, or a combination of at least two thereof.

6. The preparation method according to claim 4, characterized in that: The primary mixing includes liquid phase mixing, and the liquid phase mixing includes: primary mixing of a carbon source, a doped lithium source, a sulfur source and a solvent to obtain a doped carbon source; Preferably, when the raw materials mixed once further include a solvent, the obtained secondary mixture is a gel-state substance.

7. The preparation method according to claim 4 or 6, characterized in that: The reaction includes heat treating the secondary mixed material; Preferably, the heat treatment comprises sequentially performing a first heat treatment and a second heat treatment; Preferably, the temperature of the first heat treatment is 250-400° C., and the time of the first heat treatment is 1-10 hours; Preferably, the temperature of the second heat treatment is 600-900° C., and the time of the second heat treatment is 5-24 hours.

8. The preparation method according to claim 4, characterized in that: Performing chromium ion implantation treatment on the product obtained after the reaction; Preferably, the product after the reaction is first subjected to a grinding treatment, and then subjected to an ion implantation treatment of chromium ions; Preferably, during the ion implantation process, the ion voltage is 90 to 120 keV; Preferably, during the ion implantation process, the amount of chromium ions implanted is 5×10 10 ions / cm 2 ~9×10 11 ions / cm 2 ; Preferably, during the ion implantation process, the vacuum degree is less than 1×10 -5 Pa.

9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Mixing a carbon source, a lithium source, a sulfur source and a solvent at one time, wherein the molar ratio of the carbon source to the sulfur source is 50:(0.5-2), and the molar ratio of the carbon source to the doped lithium source is 50:(0.5-2), to obtain a doped carbon source; secondary mixing and doping the carbon source, the first lithium source, the phosphorus source, the manganese source and the iron source to obtain a gel-state substance; The gel-state substance is subjected to a first heat treatment at 250-400° C. for 1-10 hours, and then the temperature is raised to 600-900° C. for a second heat treatment for 5-24 hours to obtain a reaction product; The reaction product is ground to a vacuum degree of less than 1×10 -5 Pa, the ion implantation voltage was 90-120 keV, and the ion implantation volume was 5×10 10 ions / cm 2 ~9×10 11 ions / cm 2 , obtaining the lithium manganese iron phosphate positive electrode material.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material as described in any one of claims 1 to 3 or the lithium iron manganese phosphate positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Preparation method of lithium ferromanganese phosphate composite

    CN107046128A

  • Lithium iron manganese phosphate powder material as well as preparation method and application thereof

    CN111710846A

Cited By

  • Composite positive electrode material, preparation method thereof and secondary battery

    CN120878809A